ANALISIS STRATEGI KOMUNIKASI PEMASARAN MELALUI PENDEKATAN STOP-SIT (STUDI KASUS TERHADAP PT. DIANSYAH DINAMIKA WIRYAMANTA) - Adika Fadhlurrahman, (2020)
This research was made based on the increasing needs of the Indonesian people for an increasingly large entertainment, the increase will lead to a domino effect, if the enthusiasm is greater then the competition that appears will be tighter. This makes advertising service providers, especially event organizers, to develop very rapidly, and become more creative with the aim of increasing service users and winning competition among competitors. The purpose of this research is to find out how the marketing communication strategy carried out by PT. Diansyah Dinamika Wiryamanta to increase service usage and win competition in the event organizer business. The research method used is a qualitative type with descriptive study analysis. Data collection through in-depth interviews, observation, and documentation. The main concepts used are STOP-SIT analysis and marketing communication strategies. The results of this study indicate that PT. Diansyah Dinamika Wiryamanta carries out a marketing communication strategy by prioritizing the mix of interactive / internet marketing, personal selling, sales promotion, and public relations. PT. Diansyah Dinamika Wiryamanta positions itself to clients based on use / application positioning and forms a brand image based on the image owned by the brand itself. PT. Diansyah Dinamika Wiryamanta uses the Top Down marketing communication strategy planning model, in planning the marketing communication strategy of PT. Diansyah Dinamika Wiryamanta applies a plan based on distinctive competence. Researchers also concluded that PT. Diansyah Dinamika Wiryamanta has carried out an effective and efficient communication strategy activity, PT. Diansyah Dinamika Wiryamanta has conducted an internal analysis of the selection of communication strategies used, and to create a close relationship with clients it is necessary to do a constant and continuous communication. Suggestions for SEM (search engine marketing), more interactive in conducting marketing communication mix activities.